2020
DOI: 10.3390/cells9122558
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effectiveness of Mesenchymal Stem Cells of the Placenta and Their Conditioned Medium in Local Radiation Injuries

Abstract: Background: The search for an effective therapy for local radiation injuries (LRI) is urgent; one option is mesenchymal stem cells (MSC) derived from the placenta and their conditioned medium for the regenerative processes of the skin. Methods: We used 80 animals, randomly assigned to four groups: control (C) animals that did not receive therapy; control with the introduction of culture medium concentrate (CM); introduction of MSCs (PL); introduction of CMPL. LRI modeling was performed on an X-ray machine at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Modeling of the relatively "soft" X-ray radiation of LRIs was carried out using an LNK-268 X-ray unit (RAP100-10) (Diagnostics-M, Moscow, Russia) with the following irradiation mode: dose, 110 Gy; a 0.1 mm thick aluminum filter; voltage, 30 kV; beam current, 6.1 mA; and dose rate, 21.1 Gy/min for 312 s (dose accuracy ± 5%, dose measurement uncertainty ± 6%) according to the previously proposed method [19,60,61], leading to a short latency period and chronic skin ulcers in the laboratory animals. After irradiation, the animals were seated in individual sterile boxes with an autonomous smart flow ventilation system (Tecniplast Group, Buguggiate, Italy) with unlimited access to water and food.…”
Section: Modeling Of Local Radiation Injuriesmentioning
confidence: 99%
“…Modeling of the relatively "soft" X-ray radiation of LRIs was carried out using an LNK-268 X-ray unit (RAP100-10) (Diagnostics-M, Moscow, Russia) with the following irradiation mode: dose, 110 Gy; a 0.1 mm thick aluminum filter; voltage, 30 kV; beam current, 6.1 mA; and dose rate, 21.1 Gy/min for 312 s (dose accuracy ± 5%, dose measurement uncertainty ± 6%) according to the previously proposed method [19,60,61], leading to a short latency period and chronic skin ulcers in the laboratory animals. After irradiation, the animals were seated in individual sterile boxes with an autonomous smart flow ventilation system (Tecniplast Group, Buguggiate, Italy) with unlimited access to water and food.…”
Section: Modeling Of Local Radiation Injuriesmentioning
confidence: 99%
“…57 In vivo experimental animal models can be used in the form of mice, 53 rats, 55 and pigs. 21 This method has been tested on animal models with various conditions, such as chronic wounds, 58 burns, 38 diabetic foot ulcers, 71 skin ulcers, 53 and radiation wounds, 72 which require special handlers. The results showed that wound treatment with secretome was able to accelerate wound healing by increasing the effect of cell migration and proliferation and triggering angiogenesis, re-epithelialization, neovascularization and deposition of collagen that play a role in the wound healing process.…”
Section: Wound Healingmentioning
confidence: 99%
“…Topical application of a mixture of different stem cells such umbilical cord mesenchymal stem cells and other regenerative medicine products in a patient with an irradiated perineal wound after anal squamous cell cancer and flap failure resulted in wound healing after 79 days [ 3 ]. Application of conditioned mesenchymal stroma cells in severe local radiation injuries accelerated wound healing [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%